The autobiography of a teacher as a methodology and diagnosis in higher education - Calderón-Jaramillo, Ana (2019)
Investigating the subjectivity of the teacher of higher education allows us to reveal the complex network of relationships that are intertwined in these spaces of knowledge, identify the different ways in which students learn a certain conceptual framework and recognize the appropriate strategies to propose an innovative diagnosis that Contribute to a real improvement of reflection processes in students. The research developed addressed the subject of political subjectivity in higher education, in the light of qualitative epistemology and grounded theory. As part of its objectives, it was proposed to investigate the teaching subjectivity, complementing the analysis from different angles. One of the results was to recognize the potential of autobiography as a method of inquiry of teaching subjectivity, which allows the understanding of the different positions that the subject makes around controversial issues, disciplinary content, and particularly, on politics. It was concluded that analyzing what students, teachers and researchers produce, allow the emergence and detachment of reflections on oneself as strategies for meaningful learning and the permanent renewal of new subjective senses.